GROWTH, NETT ENROLLMENT RATIO AND CONVERGENCE OF HUMAN DEVELOPMENT INDEX - Joko Susanto (Journal of Applied Economics in Developing Countries, 2018)
This study  analyses the convergence of Human Development Index (HDI) and contribution of growth and nett enrollment ratio in supporting this convergence based on a set panel data comprising 6 regency and 1 city in Former  Surakarta Residency from 2007 to 2017. The data published by the Statistics of Jawa Tengah Province is used in this study. The results show that there is an convergence of Human Development Index (HDI)  in Former  Surakarta Residency.  Therefore, Human Development Index in the lagging regions, tends to grow faster than advanced ones. The gap of Human Development Index among regions will disappear. The growth and nett enrollment ratio  have positive impact in supporting convergence of Human Development Index. Better growth and nett enrollment ratio encourage lagging region tend to catch up with advanced ones.Keywords: Human Development Index, Growth, Nett Enrollment Ratio, Convergence